Comprehensive semisyntheses of catathelasmols C, D, and E from D-glutamic acid, utilizing lipase-catalyzed site-selective reactions on intermediates. Issue 7 (2nd July 2020) - Hashiba, Rinta; Hashimoto, Riichi; Nishiguchi, Momoko; Kobayashi, Toshifumi; Hanaya, Kengo; Higashibayashi, Shuhei; Sugai, Takeshi
ABSTRACT: Catathelasmols C, D, and E, which had been isolated from Catathelasma imperiale as inhibitors for 11-hydroxysteroid dehydrogenases, were comprehensively semisynthesized from commercially available D-glutamic acid. The key synthetic intermediate, ( R )-pentane-1, 2, 5-triol, was site-selectively acetylated by treatment with vinyl acetate and Candida antarctica lipase B (Novozym 435) in tetrahydrofuran (THF) at 25°C to furnish 1, 5-diacetate (catathelasmol E, quantitative). The acetylation occurred site-selectively on the primary alcohols at the C-1 and C-5 positions over the secondary alcohol at the C-2 position. Dichromic acid oxidation provided 2-oxopentane-1, 5-diyl diacetate (catathelasmol C, 78%). Burkholderia cepacia lipase-catalyzed transesterification with methanol in THF at – 5°C proceeded preferentially on the acetate at C-1 located adjacent to the C-2 carbonyl group over the other terminal acetate at the C-5 position. 5-Hydroxy-4-oxopentyl acetate (catathelasmol D) was obtained in 53% yield. GRAPHICAL ABSTRACT: uf0001 Catathelasmols (C, D, and E), inhibitors for 11-hydroxysteroid dehydrogenases, were comprehensively semisynthesized from commercially available D-glutamic acid. Key steps: lipase-catalyzed site-selective acylation and deacetylation